2010
DOI: 10.1109/jproc.2009.2030699
|View full text |Cite
|
Sign up to set email alerts
|

GaN Substrates for III-Nitride Devices

Abstract: | Despite the rapid commercialization of III-nitride semiconductor devices for applications in visible and ultraviolet optoelectronics and in high-power and high-frequency electronics, their full potential is limited by two primary obstacles: i) a high defect density and biaxial strain due to the heteroepitaxial growth on foreign substrates, which result in lower performance and shortened device lifetime, and ii) a strong built-in electric field due to spontaneous and piezoelectric polarization in the wurtzite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
85
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(88 citation statements)
references
References 113 publications
(131 reference statements)
0
85
0
3
Order By: Relevance
“…As suggested by early literature, the vibrational state of H2 is the main contribution under high growth temperature [56,62]. Besides this method, we noticed that another quantifiable relation of the quantity ∆ H is [95] 2N∆ H = , (8) where N is the number of H2 molecules, G is the Gibbs free energy of H2 (gas) in reference to zero temperature. Therefore, in this paper, we refer to the experimental data of H2(gas) Gibbs free energy G [96], including both enthalpy and entropy contributions, to obtain the quantitative relation of the expression aforementioned.…”
Section: Fig 5 Calculated Absolute Interface Energies With the Confmentioning
confidence: 79%
See 1 more Smart Citation
“…As suggested by early literature, the vibrational state of H2 is the main contribution under high growth temperature [56,62]. Besides this method, we noticed that another quantifiable relation of the quantity ∆ H is [95] 2N∆ H = , (8) where N is the number of H2 molecules, G is the Gibbs free energy of H2 (gas) in reference to zero temperature. Therefore, in this paper, we refer to the experimental data of H2(gas) Gibbs free energy G [96], including both enthalpy and entropy contributions, to obtain the quantitative relation of the expression aforementioned.…”
Section: Fig 5 Calculated Absolute Interface Energies With the Confmentioning
confidence: 79%
“…the major difficulty in the p-type doping. Meanwhile, lacking of low cost and lattice matched substrates remains a big challenge for many group III-nitrides [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The comparison of photoluminescence of the GaN layers deposited on the Al face and on the N face of the single-crystal AlN substrate showed that in the former case photoluminescence is consistent with that of the homoepitaxial Ga-face GaN while in the latter an existance of the tail localized states was found (Tamulatis et al, 2003). The studies of deep-UV emission of AlGaN quantum wells (Gaska et al, 2002) as well as AlGaN UV (Nishida et al, 2004a;Ren et al, 2007;Xi et al , 2006a) and InGaN MQW green (Cartwright et al, 2006) LEDs grown on the bulk AlN substrates and blue and UV LED on the bulk GaN substrates (Cao et al, 2004;Cao et al , 2004a;Du, Lu, Chen, Xiu, Zhang & Zheng, 2010) as well as cyan and green LEDs grown on a-plane (Detchprohm et al, 2008) and m-plane (Detchprohm et al, 2010) GaN bulk substrates prove the superiority of the native substrates, e.g., the luminescence intensity of the quantum well grown on bulk AlN was higher that that of the quantum well grown on SiC by a factor of 28, the noticeable improvement over LEDs grown on sapphire in device impedance and thermal characteristics (Ren et al , 2007a), the reduction in current-voltage differential resistance and in turn-on voltage (Paskova et al, 2010). The emission spectrum of AlGaN-based UV-LEDs on a bulk AlN substrate under the high current injection is much more stable than that of LEDs fabricated on the conventional substrate (Nishida et al, 2004a;.…”
Section: Epitaxial Layers and Devices On Single-crystal Native Iii-nimentioning
confidence: 86%
“…For example, the substitutional defect associated with aluminum vacancy serves as a very efficient center for the phonon scattering (Rojo et al, 2001). 4 For example, in GaN crystals grown by the hydride (halide) vapour-phase epitaxy (HVPE) an unintentional n-type conductivity originates from the background doping by silicon and oxygen from the quartz elements of the reactor or from the process gases (Paskova et al, 2010). Fe compensating doping allows one to achieve semi-insulating properties of the layer in this growth method (Vaudo et al, 2003) with the the lowest free carrier concentration reported so far 5 · 10 13 cm −3 (Paskova et al, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation